Non-destructive methodologies applied to track the occurrence of natural micropollutants in watering: Glycine max as a biomonitor - Iriel, Analia (2019)
Groundwater is habitually used for watering purposes in rural areas where the rainfall is not enough to adequately cover the crop requirements. However, groundwater sources could be naturally contaminated with trace micropollutants like As and associated elements (B, V and F) adversely affecting the plant health. In this work, non-destructive methodologies based on reflectance and chlorophyll emission processes were applied to assess the presence of micropollutants in watering by using a widespread crop (soybean plant). One of the most substantial results is that the co-occurrence of As, V, B and F in the watering solution clearly produced a synergistic effect in the plants. In fact, both reflectance and fluorescence techniques were proved in this work to be effective in detecting non-destructively stress by multielement treatment. Particularly, for reflectance measurements the most sensitive parameters were the derivative peak area between 480 and 560 nm and the chlorophyll content. Furthermore, it was demonstrated that it is possible to successfully use a portable hyperspectral spectroradiometer instead of a conventional spectrophotometer as the determinations performed with both instruments were positively correlated. Concerning fluorescence, variable emission of chlorophyll-a was more sensitive to stress than steady-state emission. The parameter Fv/F0 was a valuable indicator of stress but the quantum yields of PSII and NPQ stood out as the most sensitive indices with variations of around 60 and 100% respectively.